Phylogenomic species delimitation and host‐symbiont coevolution in the fungus‐farming ant genus Sericomyrmex Mayr (Hymenoptera: Formicidae): ultraconserved elements (UCEs) resolve a recent radiation. (13th February 2017) - JEŠOVNIK, ANA; SOSA‐CALVO, JEFFREY; LLOYD, MICHAEL W.; BRANSTETTER, MICHAEL G.; FERNÁNDEZ, FERNANDO; SCHULTZ, TED R.
Abstract: Ants in the Neotropical genus Sericomyrmex Mayr cultivate fungi for food. Both ants and fungi are obligate, coevolved symbionts. The taxonomy of Sericomyrmex is problematic because the morphology of the worker caste is generally homogeneous across all of the species within the genus, species limits are vague, and the relationships between them are unknown. We used ultraconserved elements (UCEs) as genome‐scale markers to reconstruct evolutionary history and to infer species boundaries in Sericomyrmex . We recovered an average of ∼990 UCE loci for 88 Sericomyrmex samples from across the geographical range of the genus as well as for five outgroup taxa. Using maximum likelihood and species‐tree approaches, we recovered nearly identical topologies across datasets with 50–95% matrix completeness. We identify nine species‐level lineages in Sericomyrmex, including two new species. This is less than the previously described 19 species, even accounting for two species for which we had no UCE samples, which brings the total number of Sericomyrmex species to 11. Divergence‐dating analyses recovered 4.3 Ma as the crown‐group age estimates for Sericomyrmex, indicating a recent, rapid radiation. We also sequenced mitochondrial cytochrome oxidase subunit I (COI) for 125 specimens. Resolution and support for clades in our COI phylogeny are weak, indicating that COI is not an appropriate species‐delimitation tool. However, taxa within species consistently cluster together, suggesting that COI is useful as a species identification ('DNA barcoding') tool. We also sequenced internal transcribed spacer (ITS) and large subunit (LSU) for 32 Sericomyrmex fungal cultivars. The fungal phylogeny confirms that Sericomyrmex fungi are generalized higher‐attine cultivars, interspersed with Trachymyrmex‐ associated fungal species, indicating cultivar sharing and horizontal transfer between these two genera. Our results indicate that UCEs offer immense potential for delimiting and resolving relationships of problematic, recently diverged species.